Critical behavior in the vicinity of nematic to smectic A (N–SmA) phase transition of two polar–polar binary liquid crystalline systems. (2nd January 2018) - Barman, Barnali; Sarkar, Sudipta Kumar; Das, Malay Kumar
ABSTRACT: Phase diagram, critical behavior and order of the nematic (N)–smectic A (SmA) phase transition of two polar–polar binary systems (i) 4- n -heptyloxy-4′-cyanobiphenyl (7OCB) and 4- n -octyloxy-4′-cyanobiphenyl (8OCB); (ii) 4- n -octyloxy-4′-cyanobiphenyl (8OCB) and 4- n -nonyloxy-4′-cyanobiphenyl (9OCB) by means of a high-resolution temperature scanning measurement of birefringence have been reported in this work. A simple power law analysis has been adopted to extract the specific heat critical exponent (α′) at N–SmA transition from birefringence data. The α′ for N–SmA transition indicates a uniform crossover behavior and has appeared to be non-universal in nature. With increasing concentration of the higher homologues for both the binary systems, the N–SmA transition reveals a strong tendency to be driven towards the tricritical nature. The 3D- XY limit (i.e. α′ = −0.007) for N–SmA transition reaches at the concentration x 8OCB = 0.28 corresponding to the McMillan ratio 0.914, whereas the tricritical point has been found to appear near x 9OCB = 1.0 corresponding to McMillan ratio 0.992.